VÍTOR OLIVEIRA - Urban Morphology and Human Settlements - Llop Torné, Carles (ZARCH, 2025)
VÍTOR OLIVEIRAISUF, Urban Morphology and Human SettlementsSpringer, Cham (Suiza), 2024, 274 pp. Tapa blanda y tapa dura. 145 €Idioma: inglésHARDCOVER ISBN: 978-3-031-58135-9SOFTCOVER ISBN: 978-3-031-58138-0